Measurement of the Maturity Level of IT Governance in Implementing Personnel Management Information System Using the MEA Domain COBIT 5 Framework In Regional Personnel, Education and Training Agency - Stanny Dewanty Rehatta; Augie David Manuputty (Journal of Information System and Informatics, 2019)
BKDIKLATDA in Salatiga is an Personnel Institution located in the Salatiga City Government area, which is currently implementing IT as a supporter of business processes. One of the IT used is the Personnel Management Information System (SIMPEG). SIMPEG is a system specifically designed to provide personnel administration management information quickly, accurately and accurately, and has the function to manage staffing data and information in the working environment of the Salatiga Municipal Government. In this study COBIT 5 was used specifically the Monitor, Evaluate, Assessment (MEA) domain to observe, evaluate and evaluate the performance of IT governance on the application of SIMPEG in the Salatiga City BKDIKLATDA. MEA is a domain in COBIT 5 whose purpose is to observe, evaluate and assess all processes related to IT in a company or organization. The purpose of this study was to help the Salatiga City BKDIKLATDA to optimize the SIMPEG process performance and find out the level of maturity and the ability to apply SIMPEG in the Salatiga City BKDIKLATDA. The research methodology used in this study is mixed method. Mixed method is a research approach that combines or links qualitative and quantitative research methods. The results of this study are expected to optimize the effective and efficient performance process in the application of SIMPEG in the Salatiga City BKDIKLATDA so that in the future it will be even better.